Effect of aqueous tetrapleura tetraptera (African porridge fruit) on performance and gut morphology of broiler chickens (2014)
A study was conducted for 8 weeks to determine the effect of administering varying levels of aqueous Tetrapleura tetraptera (African porridge fruit) on performance and gut morphology of broilers. A total of 150 day old broiler chicks (Abor acre) were randomly selected and allotted to 5 treatments and C replicates per treatment. The experimental ingredient was extracted and served to the birds in the 5 different treatments as follows; Control (water with no additive), Positive control (antibiotics), 3, 6 and 9mis respectively. Total weight gain, feed intake and feed conversion efficiency were not (P>0.05) significantly different across the varying-levels of Tetrapleura tetraptera administered. There were also no differences in feed conversion ratio of birds administered with Tetrapleura tetraptera compared with those on antibiotics. Broiler's gut parameters measured indicated that there were no significant differences (P>0.05) across the varying levels of the Tetrapleura tetraptera extract administered on the broilers. The study demonstrated that administration of Tetrapleura tetraptera extract in water for broilers compared favorably with birds on antibiotics though no significant differences were recorded.